Application of the new electroanalytical technique AGNES for the determination of free Zn concentration in river water - Zavarise, Francesca; Companys, Encarnació; Galceran, Josep; Alberti, Giancarla; Profumo, Antonella (Analytical and bioanalytical chemistry, 2010)
Absence of gradients and Nernstian equilibrium stripping (AGNES) is a recently developed electroanalytical technique specifically designed for the direct determination of free concentrations of metal ions. AGNES is applied here to the determination of free Zn concentration in a river water sample. The method has been validated with synthetic solutions of low ionic strengths containing Zn and 2,6-pyridinedicarboxylic acid and then applied to synthetic river waters and to a natural sample collected from Besòs River in Montcada i Reixac (Catalonia, North-Eastern Spain). In the river sample, an average free Zn concentration of 12.8(4) nM was obtained, while the total dissolved Zn concentration was 0.51(8) μM. To control and maintain pH and pCO₂ constant during AGNES measurements, a novel device for N₂/CO₂ mixed purging has been developed.